MULTIFACETOR RISK ANALYSIS OF LOCAL COMPLICATIONS OF AN INTESTINAL STOMA AS A BASIS FOR PERSONALIZED REHABILITATION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
The formation of an intestinal stoma is accompanied by a high risk of local complications, which significantly limit the effectiveness of postoperative rehabilitation. Modern concepts indicate the multifactorial nature of complications, however, in clinical practice, there is a tendency to isolated assessment of risk factors without their integration into a single decision-making system.